STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) MELALUI PAJAK DAERAH DI KOTA MALANG (STUDI PADA DINAS PENDAPATAN DAERAH KOTA MALANG) - Sahroni, Rohmat Hafinudin (Jurnal Mahasiswa Perpajakan, 2015)
Good local tax management made maximum acceptance of local tax. UU No. 23 year 2014 about local tax and local retribution is the main reference for local tax management in indonesia. the goal of this research is to find supported and resisted factor that affect the local tax income in Malang city from local tax sector and to find the strategy to increase local tax income as an local income In malang city. This research use descriptive method with qualitative approach. The result of this research show that workplan of DISPENDA Malang city was work well. Supported factor that can increase local tax income in malang city are two things, first the supporting infrastructures and second good information system. resisted factor is the weakness of taxpayer discipline and different quality ofÂ  Human resource in DISPENDA Malang City. Strategy that used by DISPENDA to increase local tax income is from Intensification and extension program. Intensification program include tax rate adjustment, supervision enhancement and controlling local tax payment, Human resource development and income target planing. extension program include field survey, coordination and cooperate with related institution and do some socialization. SWOT Strategy annualize is to optimize Intensification and extension strategy , Build UPTD, boost socialization , and Skill development in DISPENDA. supervision enhancement and evaluation to DISPENDA apparatus, change of Local Rule, and do instance training to DISPENDA apparatus especially in Technology and information. Keyword: Local tax optimization, Intensification and extension of local tax, SWOT analyzed